Overcoming Bad Leadership in Organizations 2022
DOI: 10.1093/oso/9780197552759.003.0013
|View full text |Cite
|
Sign up to set email alerts
|

How to Mitigate Destructive Leadership

Abstract: Leaders with Dark Triad traits (Machiavellianism, psychopathy, and narcissism) are notorious for their display of destructive behavior in interacting with their subordinates. It may be argued that organizations have the obligation to protect the organization as a whole as well as the people in it from the damaging effects that these leaders have. The authors posit that the human resource management teams may be best suited to accomplish that goal. In this chapter, the authors outline a theoretical model explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Third, organizations should try to create an environment that convincingly establishes employee well-being, mutual respect, and trust as core values, instead of promoting a getting-ahead-at-all-costs mentality. Effective complaint systems and disciplinary procedures have to be in place, and employees should be encouraged to use these without fear of reprisal (e.g., Schyns et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Third, organizations should try to create an environment that convincingly establishes employee well-being, mutual respect, and trust as core values, instead of promoting a getting-ahead-at-all-costs mentality. Effective complaint systems and disciplinary procedures have to be in place, and employees should be encouraged to use these without fear of reprisal (e.g., Schyns et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Machiavellian individuals, who are extremely concerned with their interests and unconcerned with the interests of others and the collective interests, are likely to violate the principle of fair social exchange between individuals and between individuals and organizations, thus engaging in unethical behavior is harmful to others and organization (Koo and Lee, 2022). Previous studies have found that subordinates of Machiavellian leaders report more abusive supervision (Schyns et al, 2022). The positive effect of ethical leadership on subordinate engagement is also lower among highly Machiavellian leaders (Den Hartog and Belschak, 2012).…”
Section: Promotion Workplace Anxiety and Leadershipmentioning
confidence: 98%
“…Third, organizations should try to create an environment that convincingly establishes employee well-being, mutual respect, and trust as core values, instead of promoting a getting-ahead-at-all-costs mentality. Effective complaint sys-tems and disciplinary procedures have to be in place, and employees should be encouraged to use these without fear of reprisal (e.g., Schyns et al, 2022).…”
Section: Practical Implicationsmentioning
confidence: 99%